Effect of fiber chemical modifications on the abaca fiber reinforced unsaturated polyester matrix composite - Hagad, Stela Marie C. (2009.)
Abaca (Manila hemp) fiber has been recently used as reinforcing material to various polymer matrix composite products. Further studies are, however, needed to make this fiber more compatible with the polymer matrix such that it can better reinforce the polymer matrix composite. In this study, improved reinforcing capacity of the abaca fiber is explored by subjecting it to treatments with alkali, nitric acid, acetic anhydride and their combinations in order to improve the mechanical property of abaca fiber reinforced unsaturated polyester composite through enhancement of the interfacial adhesion of the abaca fiber and the unsaturated polyester. Four different procedures of alkali treatments were employed. First, 5% NaOH for 1 hr at room temp; second, a series of 1% and 5% NaOH for 1 hr each at 94-96 degree Celsius; third and fourth involved the mercerization of fiber in 18% NaOH for 2 hrs at room temperature with further exposure to 3% NaOH for 1 hr at 94-96 degree Celsius without and with neutralization with acetic acid, respectively. Density, moisture regain and tensile strength of the untreated and treated fibers were monitored as well as changes in fiber structure as a result of the treatments employed since these parameters are considered influential to the interaction between the reinforcing fiber and matrix. Interfacial adhesion was evaluated through dynamic fiber pull-out of the untreated and treated fibers. Untreated and treated fibers were arranged unidirectionally to reinforce unsaturated polyester matrix. Mechanical testing was done on the composite to determine the effect of the treatments employed. Morphological characterization of the fiber and fracture surface analyses of the composite was also conducted. Results showed that the density, moisture regain, and tensile strength of the fiber were significantly changed due to the treatments employed. While the tensile strength and moisture regain of the fiber was found to decline as fiber were mercerized and exposed to heat treatment, a positive increase in density was observed for mercerized fiber neutralized with acetic acid and further treated with acetic anhydride. Same fiber yielded a great improvement in fiber/matrix interfacial adhesion as evidenced by the dynamic fiber pull out test. The resulting composite was also showed the highest strength of 70.2 MPa, which is higher by 1.47 times the untreated fiber-reinforced composite at 5% fiber volume. Microscopy analyses of the fracture surface further confirmed the improved adhesion between fiber and matrix as evidenced by the longer fiber pull outs for the untreated fiber composite and clean fiber cut near the fracture surface for the mercerized abaca fiber composite.
"May 2009."
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman.
Keywords: Fiber Industry Development Authority -- Philippines -- Leyte; Abaca (Fiber) -- Philippines -- Leyte; Reinforced plastics -- Philippines -- Leyte; Composite materials -- Philippines -- Leyte